The Criminalization of Child Marriage by Parents under Law Number 12 of 2022 - Nazwa Bunga Rezky Perdana Lubis; Iwan Iwan (Hakamain: Journal of Sharia and Law Studies, 2026)
This study aims to analyze parental criminal liability for child marriage under Article 10 of Law Number 12 of 2022 on the Crime of Sexual Violence and examine its legitimacy from the perspective of Fiqh Jinayah (Islamic criminal jurisprudence) in relation to the principle of geen straf zonder schuld (no punishment without culpability). The study employs normative legal research using statutory and conceptual approaches, with legal materials analyzed qualitatively through grammatical, systematic, and teleological interpretation. The findings indicate that parental criminal liability should not arise solely because parents facilitate or consent to child marriage but must be supported by proof of coercion, abuse of authority, and criminal culpability. Accordingly, Article 10 should be applied on a case-by-case basis to distinguish coercive conduct from parental involvement influenced by social, economic, cultural, or pregnancy-related circumstances, thereby preventing overcriminalization while ensuring effective child protection. From the perspective of Fiqh Jinayah, forced child marriage constitutes ta'addī (unlawful transgression) that may justify ta'zīr (discretionary criminal sanctions), whereas wilāyah al-ijbār (guardianship with compulsory authority) requires contextual interpretation based on maqāṣid al-sharī'ah (objectives of Islamic law). The study concludes that criminal sanctions achieve substantive justice only when applied proportionally by considering culpability and the surrounding social context. This study contributes to criminal law and Islamic legal scholarship by proposing an integrated normative framework that reconciles the principle of culpability with Fiqh Jinayah, providing doctrinal guidance for interpreting parental criminal liability while contributing to the global discourse on balancing child protection, proportional criminal liability, and legal pluralism.